Lieselotte Friedlaender (1898 - 1973) eine Künstlerin der Weimarer Republik ; ein Beitrag zur Pressegraphik der zwanziger Jahre ; mit einem Verzeichnis der Werke 1920 bis 1933 - Dogramaci, Burcu 1971- (Wasmuth, 2001)
Presents an extensive account of the life and work of the German graphic artist and fashion illustrator Lieselotte Friedlaender (1898-1973), concentrating on her efforts between 1920 and 1933, along with a catalogue raisonné of her work during those years. The catalogue includes 481 entries and a title index to the works. The book contains 102 black and white illustrations and 20 in color.
Verz. der Werke 1920 - 1933 S. 197 - 247. - Titelverz. S. 248 - 254
Keywords: @Friedlaender, Lieselotte <1898-1973> - Catalogues raisonnés; @Friedlaender, Lieselotte <1898-1973> - Critique et interprétation; Friedlaender, Lieselotte <1898-1973> -- Catalogues raisonnés; Friedlaender, Lieselotte -- 1898-1973; Geschichte 1920-1933; Kunst; Kunstgeschichte; Persönlichkeit, Kunst; Grafikdesign; Kleidung -- Motiv; Modezeichnung; Deutschland; Hochschulschrift; Werkverzeichnis